Quando o ativismo de fã-gamers entra em jogo: participação, resistências e práticas do Fandom de League of Legends no Brasil - MACEDO, Tarcízio Pereira (Universidade Caxias do Sul, 2023)
From the understanding of fan activism as a form of everyday resistance, cultural, economic and creative, the goal of this job is to understand how and at what point the consumption of fan-garners becomes a political and civic participation, from a methodological triangulation with emphasis on the use of ethnographic inspirations. While empirical support, presents a mapping on some practices of fan-garners activism in the former official forum of the online game of League of Legend (LoL) in Brazil. Thus, propose is a typology of daily resistance practices in the LoL community in four different ways. The results of the approach indicate that the diversity of the universe of digital productions and practices of these fans re-signifies understandings of resistance and question the duality between citizenship and the consumption of pop culture, acting as catalysts that provide a variety of practices that (re)interpret and exceed the limits of the fandom.